Kant’s appearance as an objective-objectual [gegenständlich] representation - Katrechko S. L. (Кантовский сборник, 2017)
This article analyses the features of Kant’s [transcendental] philosophy, which Kant himself described as transcendental idealism. On the one hand, Kant’s transcendentalism rests on the distinction between things-in-themselves and appearances. On the other hand, our method of cognition is representative in that is based on representations — subjective and objective (objectual) ones. A synthesis of the above considerations suggests that Kant’s transcendentalism rests on the [conceptual] triad — ‘[objective] object (thing-in-itself; Ding an sich) —appearance (Erscheinung) — and [mental] representation (Vorstellung)’. Kant’s transcendental philosophy is impossible without the concept (‘premise’) of appearance (a paraphrase of Friedrich Jacobi’s maxim). It is the third complete entity, which has an intermediate ontological and epistemological status. Appearance can be correlated with objective (objective-objectual ‘gegenstänslich’) representation. It would be unwise to identify appearance with thing-in-itself, which was characteristic of pre- Kantian philosophy (naïve realism), or appearance with representation, which was the case in phenomenalist interpretations of transcendentalism à la Berkley (interpretation of two objects). Kant’s appearance, as emphasised in BXXVII of his Critique, is an appearance of an object (thing-initself), which — although implicitly — suggests a semantic relationship of reference. Appearance (as a sign) is impossible without what appears in it (the referent of a sign). This article puts forward a number of arguments in favour of the objective/objective-objectual status of Kant’s concept of appearance.